A CONSPECTUS OF BALINESE OLEACEAE - Yessi Santika (Floribunda, 2016)
Yessi Santika. 2016. Ikhtisar suku Oleaceae di Bali. Floribunda 5(5): 175–177. — Uraian pendek suku Oleaceae di Bali disajikan dan tujuh jenis tumbuhan dicatat. Jenis-jenis tersebut adalah Chionanthus ramiflorus Roxb., Fraxinus graffithii C.B. Clarke, Jasminum multiflorum (Burm.f.) Andr., Jasminum sambac (L.) Aiton, Ligustrum glomeratum Blume, Olea paniculata R.Br. dan Myxoporum nervosum Blume. Keberadaan Myxoporum nervosum dan Jasminum sambac merupakan rekaman baru untuk Bali.Kunci identifikasi, pertelaan singkat dan area distribusi dari masing-masing jenis disajikan.Yessi Santika. 2016. A Conspectus of Balinese Oleaceae. Floribunda 5(5): 175–177. — A short account of Balinese Oleaceae is presented and seven species are recorded. There are Chionanthus ramiflorus Roxb., Fraxinus graffithii C.B. Clarke, Jasminum multiflorum (Burm.f.) Andr., Ligustrum  glomeratum Blume, Olea paniculata R.Br., Jasminum sambac (L.) Aiton and Myxoporum nervosum Blume. The last two species are new recorded for Bali.Identification key, short descriptions and distribution areas for each species are given.